A dopamine hybrid ligand ZIF-8 / gelatin composite aerogel and its preparation method and application
By designing a composite aerogel of dopamine hybrid ligand ZIF-8 and gelatin, the problems of insufficient thermal stability and particle aggregation of traditional MOF materials are solved, and the development of high-performance thermal insulation and flame retardant materials is realized, which is suitable for industrial thermal management systems.
Patent Information
- Application Number
- CN202510104890.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-23
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2045-01-23
AI Technical Summary
Existing aerogel materials have shortcomings in thermal management and flame retardant properties, especially the thermal stability of traditional MOF materials is not strong and prone to problems such as particle aggregation and insufficient interaction.
By designing the dopamine hybrid ligand ZIF-8, its crystallization rate is controlled, and a nanoporous structure with high dispersion, stability and rich functional groups are formed, and a composite aerogel is prepared with gelatin through multiple chemical crosslinking reactions and freeze-thaw gel technology.
It has realized the development of high-performance thermal insulation and flame retardant materials, with low density, high specific surface area, low thermal conductivity and good flame retardant properties, and is suitable for industrial thermal management systems.
Smart Images

Figure CN119529374B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of composite aerogels and preparation thereof, and in particular to a dopamine hybrid ligand ZIF-8 / gelatin composite aerogel and a preparation method and application thereof. Background Art
[0002] The rapid development of modern industry has led to major energy consumption problems, and it is necessary to develop high-performance thermal management materials to meet the needs of energy conservation and emission reduction. Traditional insulation materials such as asbestos, glass fiber and polyurethane often cause certain environmental pollution problems. Aerogels with lightweight, porous and high specific surface area characteristics show great potential in building insulation and industrial pipeline insulation. Typical silica aerogels have excellent thermal insulation properties due to their low thermal conductivity, but their insufficient mechanical strength poses a challenge to processing requirements. In addition, organic aerogels, such as cellulose aerogels and polyimide aerogels, have higher flexibility and formability based on rich surface chemical properties, which broadens potential thermal and mechanical applications. However, the inherent flammable physical properties make the materials prone to fire in actual environments. Therefore, there is an urgent need to develop high-performance aerogels with thermal insulation and flame retardant properties, which have great potential. These lightweight, processable and high-performance features are expected to meet the changing needs of industrial thermal management systems.
[0003] The green sustainability of biopolymer aerogels shows great advantages among many thermal insulation aerogels. Due to the abundant sources, low cost, pollution-free and multiple chemical functional groups, the obtained polymer aerogels have low bulk density and low thermal conductivity. In addition to high compatibility and natural sol properties, polymer aerogels also have strong expansion properties, which improves the comprehensive physical properties. In particular, gelatin, as a biomass polymer derived from fur and bones, is not only non-toxic, biodegradable, but also environmentally friendly, making it an ideal matrix material for aerogels. However, the inherent flammability is often overlooked, which limits the application potential of gelatin aerogels under extreme conditions such as fire. In order to overcome its flammability, inorganic nano-enhancement strategies have good potential to improve the physical properties of polymer aerogels. Since gelatin has rich functional groups (such as carboxyl, amino, hydroxyl) and low-temperature gelation characteristics, it can be precisely adjusted in structure and performance through composite reinforcement. Therefore, nano-enhanced polymer composite aerogels have important prospects in broadening the application of aerogel thermal insulation.
[0004] Metal organic frameworks (MOFs) are porous crystalline materials formed by self-assembly of metal ions and organic ligands. The highly ordered pore structure, large specific surface area and controllable chemical functions of MOFs make them have great application potential in thermal insulation. For example, the invention patent CN 116446183 B reports a MOF-loaded aramid nanofiber aerogel and its preparation method and application. By pretreating aramid nanofibers (ANF), Zr-MOF is loaded onto ANF through in-situ growth. The prepared MOF-loaded aramid nanofiber aerogel has the advantages of high MOF loading and large specific surface area. The obtained aerogel has the characteristics of structural stability, flame retardancy, heat insulation and good compression performance. Chinese patent publication number CN 117247682 A reports a biomass aerogel-based thermal insulation and flame retardant material and its preparation method. Wood fiber, carboxymethyl nanocellulose and Al-MOF nanoparticles are mixed and subjected to directional freezing and freeze-drying treatment to obtain a thermal insulation flame retardant material with low density, high porosity and low thermal conductivity. This material has broad application prospects in the field of energy-saving buildings. However, traditional MOF materials have low thermal stability, and particles are prone to aggregation during the synthesis process, and the interaction between them and the organic matrix is insufficient, which limits their thermal insulation and flame retardant properties in composite aerogels. Therefore, it is necessary to develop a new MOF nanoparticle reinforcement phase, which can enhance the thermal stability and dispersibility of MOF and enhance the interaction with the organic matrix to form an aerogel material with low density, high porosity, low thermal conductivity and good flame retardant properties. These characteristics work together to make the composite aerogel have broad application prospects in industrial thermal management systems. Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides a dopamine hybrid ligand ZIF-8 / gelatin composite aerogel and its preparation method and application. The ZIF-8-DA contains Zn 2+ -Dopamine and Zn 2+ -The dual coordination structure of dimethylimidazole, the hybrid crystals are cross-linked by covalent bonds, showing high dispersibility, stability and rich chemical functional group activity. The obtained nano-enhanced phase is evenly mixed with the gelatin solution, and the composite aerogel is prepared by multiple chemical cross-linking reactions and freeze-thaw gel technology. This material combines the nano-porosity and structural characteristics of the dopamine hybrid ligand ZIF-8 with the biocompatibility and processability of gelatin, and is a new type of high-performance thermal insulation and flame retardant material.
[0006] To achieve the above object, the present invention first provides a method for preparing a dopamine hybrid ligand ZIF-8 / gelatin composite aerogel, comprising the following steps:
[0007] S1. Preparation of dopamine hybrid ligand ZIF-8: zinc salt and dopamine hydrochloride are dissolved in deionized water as solution A, 2-methylimidazole is dissolved in deionized water as solution B, then solution A is poured into solution B and stirred rapidly to cause coordination cross-linking reaction, the obtained precipitate is washed with ethanol solution, centrifuged to remove impurities, and dried and ground to obtain dopamine hybrid ligand ZIF-8, which is marked as ZIF-8-DA;
[0008] S2. Preparation of dopamine hybrid ligand ZIF-8 / gelatin composite aerogel: the dopamine hybrid ligand ZIF-8 prepared in step S1 is homogenized at high speed in a deionized water solution, gelatin is added and stirred until completely dissolved, a cross-linking agent is dripped into the obtained slurry and continuously stirred for chemical cross-linking reaction, a glutaraldehyde solution is added and stirred, the obtained mixed hydrogel is placed in a PE mold for freeze-thaw treatment, and then thawed, and then the sample is placed on a copper plate with liquid nitrogen at the bottom and directional pre-frozen, and finally, a dopamine hybrid ligand ZIF-8 / gelatin composite aerogel ZIF-8-DA / GA is prepared by vacuum freeze-drying;
[0009] In step S2, the crosslinking agent is 3-glycidyloxypropyltriethoxysilane, the addition amount is 0.1-1wt%, the temperature of the chemical crosslinking reaction is 40-60°C, the continuous stirring time is 3-6 h, the concentration of the glutaraldehyde solution is 0.1-0.5 wt%, and the stirring time of adding the glutaraldehyde solution is 5 min.
[0010] Preferably, the zinc salt in step S1 is Zn(NO3)2·6H2O, the molar ratio of the zinc salt to 2-methylimidazole and deionized water is 1:30-70:2000-3000, and the concentration of dopamine hydrochloride is 1-4 mg / mL.
[0011] Preferably, the rapid stirring time in step S1 is 5-60 min, the coordination cross-linking reaction temperature is 30-60° C., and the time is 1-20 h.
[0012] Preferably, the dopamine hybrid ligand ZIF-8 prepared in step S1 is a rhombic dodecahedron structure with an average diameter of 500 nm.
[0013] Preferably, in step S2, the addition amount of dopamine hybrid ligand ZIF-8 is 1-4 wt %, the homogenization speed is 4000-10000 rpm, the concentration of gelatin is 2 wt %, the dissolution temperature is 40° C., and the stirring speed is 300-600 rpm.
[0014] Preferably, the temperature of the freeze-thaw treatment in step S2 is -40°C to -20°C, the time is 2-6 h, the thawing temperature is 4°C, and the time is 12-24 h; the cold trap temperature of the vacuum freeze-drying is -56°C, the vacuum degree is below 10 Pa, and the time is 72 h.
[0015] Based on a general inventive concept, the present invention also provides a dopamine hybrid ligand ZIF-8 / gelatin composite aerogel.
[0016] Based on a general inventive concept, the present invention also provides an application of a dopamine hybrid ligand ZIF-8 / gelatin composite aerogel in the preparation of a thermal insulation and flame retardant material.
[0017] The principle of the composite aerogel in this scheme having excellent thermal insulation and flame retardant properties is as follows:
[0018] Through the design of dopamine hybrid ligand MOF (i.e. ZIF-8-DA), rich functional groups were introduced, and multiple chemical cross-linking reactions occurred with gelatin under the action of cross-linking agent 3-glycidyloxypropyltriethoxysilane and glutaraldehyde solution. Not only did it strengthen the interaction between ZIF-8-DA and gelatin, but it also formed a more compact and complex three-dimensional porous pore feature, effectively reducing the gas phase thermal conductivity, thereby improving the thermal insulation performance of the material.
[0019] In addition, freeze-thaw treatment technology is used to strengthen the gel network. During the freezing process, ice crystals formed by water crystallization exert pressure on the gel network, causing the network structure to be arranged more tightly; after thawing, this tight network structure is maintained, further enhancing the mechanical strength and stability of the aerogel. At the same time, the cross-linked network can resist the destructive effect of ice crystals on the gel network and maintain its integrity, thereby ensuring the stability and thermal insulation performance of the porous pore structure; in addition, the high specific surface area nano ZIF-8-DA particles embedded in the gelatin pore wall further enhance the thermal insulation performance of the composite aerogel due to their tiny nano size, high specific surface area and high dispersibility.
[0020] The dual coordination structure of dopamine hybrid ligand ZIF-8 (Zn 2+ -Dopamine and Zn 2+ -dimethylimidazole) is cross-linked by covalent bonds, which significantly improves the thermal stability of MOF; this structure not only enhances the stability of the ZIF-8-DA particles themselves, but also solves the problem of particle aggregation that is prone to occur during the synthesis of traditional ZIF-8 materials, achieving high dispersion of the material.
[0021] During the combustion process, metal ions (such as zinc ions) in ZIF-8 can catalyze the formation of a stable carbon layer. This carbon layer effectively isolates the transfer of heat and oxygen, thereby delaying the spread of fire and improving the flame retardant properties of the material. In addition, the functional groups in the dopamine hybrid ligand (such as amino, hydroxyl, etc.) undergo cross-linking reactions with the functional groups in gelatin, which not only enhances the overall stability of the composite aerogel, but also improves its thermal shock resistance and flame retardancy. During the combustion process, these cross-linked structures can maintain the integrity of the gelatin matrix skeleton, preventing it from rapid decomposition and material collapse due to high temperatures.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] (1) This scheme uses dopamine hybrid coordination metal ions to precisely control the growth rate of ZIF-8 nanocrystals and form Zn 2+ -Dopamine and Zn 2+ -ZIF-8-DA hybrid crystals with dual coordination structure of dimethylimidazole. This stable covalent bond structure not only significantly improves the structural stability of MOF, but also effectively solves the problem of particle aggregation that is prone to occur in the synthesis process of traditional MOF materials, and achieves high dispersibility of ZIF-8-DA. In addition, ZIF-8-DA retains abundant chemical functional groups, such as amino and hydroxyl groups, which provides more possibilities for subsequent nano-enhanced gelatin-based aerogels and abundant chemical cross-linking reactions, thereby expanding the application range and performance of ZIF-8-DA in thermal insulation and flame retardancy.
[0024] (2) The ZIF-8-DA / GA composite aerogel of this scheme significantly improves the mechanical properties and chemical stability of the material through its unique three-dimensional porous microstructure. Specifically, the ZIF-8-DA nanoparticles are evenly anchored on the interconnected gelatin porous network skeleton, forming a honeycomb porous structure with relatively uniform pore sizes, mainly concentrated between 50-100μm. In contrast, pure gelatin aerogels have pore sizes of varying sizes and smooth pore wall characteristics, while the skeleton surface of ZIF-8 / GA aerogels has protrusions due to the uneven aggregation of ZIF-8 particles with poor dispersion. These differences further highlight the advantages of ZIF-8-DA / GA composite aerogels in microstructure. The Zn-MOF-DA / GA composite aerogel synthesized by the new multi-crosslinking strategy contains the porous pores of gelatin and the microporous pore characteristics of nano-MOF particles, presenting a unique three-dimensional porous microstructure.
[0025] (3) After uniformly mixing ZIF-8-DA and gelatin solution, this scheme adopts a multiple cross-linking strategy to achieve addition reaction between the epoxy group of the cross-linking agent and the amino groups of ZIF-8-DA and gelatin, thereby strengthening the cross-linking process. At the same time, the aldehyde group also undergoes Schiff base cross-linking reaction with the amino groups of ZIF-8-DA and gelatin, forming a more complex network structure. This multiple cross-linking strategy significantly improves the physical structural characteristics of the aerogel. In addition, the physical structure of the composite gel is further enhanced by freeze-thaw treatment technology. During the freezing process, ice crystals formed by water crystallization exert pressure on the gel network, causing it to be arranged more closely. After thawing, this tight network structure is maintained, thereby improving the mechanical strength and stability of the aerogel. Its compression modulus and maximum compression strength are 1.24-2.90 MPa and 0.66-1.65 MPa, respectively, which are twice and five times the maximum of GA aerogel.
[0026] (4) The ZIF-8-DA / GA composite aerogel in this scheme has a low density (0.04~0.06 g / cm 3 ), large specific surface area (154.58-433.71 m 2 / g) and three-dimensional pore structure, showing better thermal insulation and flame retardant properties than pure gelatin aerogel, with lower thermal conductivity (optimum value 32.98 mW / m·K) and smaller volume shrinkage (minimum 4.9%). In addition, ZIF-8-DA / GA composite aerogels show excellent thermal stability and flame retardant properties. Its cold surface temperature is significantly lower than that of pure gelatin aerogels in infrared thermal imaging tests, and it shows smaller volume shrinkage and smoke production in combustion experiments, which are attributed to the fire resistance of MOF nano-enhanced gelatin-based aerogels and their inhibitory effect on heat transfer. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0028] Figure 1 These are scanning electron microscope images of ZIF-8-DA and ZIF-8 in Experimental Example 1; A is a scanning electron microscope image of ZIF-8-DA, and B is a scanning electron microscope image of ZIF-8.
[0029] Figure 2 is the X-ray diffraction pattern of ZIF-8-DA and ZIF-8 in Experimental Example 1;
[0030] Figure 3is the Fourier transform infrared spectra of ZIF-8-DA and ZIF-8 in Experimental Example 1;
[0031] Figure 4 : A is a scanning electron microscope image of the ZIF-8-DA / GA composite aerogel in Experimental Example 2; A is a scanning electron microscope image at a scale of 200 μm, and B is a scanning electron microscope image at a scale of 5 μm;
[0032] Figure 5 A is a scanning electron micrograph of ZIF-8 / GA aerogel of Comparative Example 1 and GA aerogel of Comparative Example 2;
[0033] A is a scanning electron microscopy image of ZIF-8 / GA aerogel at a scale of 200 μm, and B is a scanning electron microscopy image at a scale of 5 μm; C is a scanning electron microscopy image of GA gel at a scale of 200 μm, and D is a scanning electron microscopy image at a scale of 5 μm;
[0034] Figure 6 The stress-strain curves of the ZIF-8-DA / GA composite aerogel of Experimental Example 3 and the aerogel of Comparative Example 1-2;
[0035] Figure 7 C1s and N1s high-resolution spectra of the ZIF-8-DA / GA composite aerogel of Experimental Example 4 and the GA aerogel of Comparative Example 2, A is the C1s high-resolution spectrum, and B is the N1s high-resolution spectrum;
[0036] Figure 8 Infrared thermal imaging images of the ZIF-8-DA / GA composite aerogel of Experimental Example 5 and the aerogel of Comparative Example 1-2;
[0037] Fig. 9 Thermogravimetric analysis curves of the ZIF-8-DA / GA composite aerogel of Experimental Example 6 and the aerogel of Comparative Example 1-2;
[0038] Fig.10 This is a combustion experiment of the ZIF-8-DA / GA composite aerogel of Experimental Example 7 and the aerogel of Comparative Examples 1-2. DETAILED DESCRIPTION
[0039] In order to make the technical problems, technical solutions and advantages to be solved by the present invention more clear, a detailed description will be given below with reference to the accompanying drawings and specific embodiments.
[0040] The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention. Without departing from the spirit and substance of the present invention, modifications or substitutions made to the methods, steps or conditions of the present invention are within the scope of the present invention.
[0041] Unless otherwise specified, the technical means used in the examples are conventional means well known to those skilled in the art; unless otherwise specified, the reagents used in the examples are commercially available.
[0042] Example 1 Preparation of dopamine hybrid ligand ZIF-8 / gelatin composite aerogel.
[0043] S1. Preparation of dopamine hybrid ligand ZIF-8 (ZIF-8-DA):
[0044] 5.17 g Zn(NO3)2·6H2O and 0.36 g dopamine hydrochloride were weighed and dissolved in 80 mL deionized water as solution A, and 49.26 g 2-methylimidazole was dissolved in 100 mL deionized water as solution B. Then solution A was quickly poured into solution B and stirred for 5 min. After mixing, the molar ratio of Zn(NO3)2·6H2O, 2-methylimidazole and water was 1:60:2000, and the concentration of dopamine hydrochloride was 2 mg / mL. Then, the reaction was immersed at 30°C for 2 h to cause coordination cross-linking reaction. The obtained precipitate was washed with ethanol solution and centrifuged to remove impurities. Finally, dopamine hybrid ligand ZIF-8 was obtained by drying and grinding, which was marked as ZIF-8-DA.
[0045] S2. Preparation of dopamine hybrid ligand ZIF-8 / gelatin composite aerogel ZIF-8-DA / GA:
[0046] 1wt% ZIF-8-DA prepared in step S1 was homogenously dispersed in 50 mL of deionized water solution at 4000 rpm, and then 1 g of gelatin was added and stirred at 40℃ and 300 rpm until completely dissolved. 0.1wt% crosslinker 3-glycidyloxypropyltriethoxysilane was added to the obtained slurry, and stirred at 40℃ for 6 h to promote chemical crosslinking. Subsequently, 0.1wt% glutaraldehyde solution was added to further enhance the gelation process. The obtained hybrid hydrogel was placed in a PE mold for freeze-thaw treatment, frozen at -40℃ for 2 h, and then thawed at 4℃ for 24 h. The sample was then placed on a copper plate with liquid nitrogen at the bottom and pre-frozen in a directional manner. Finally, the composite aerogel was prepared by vacuum freeze drying at a cold trap temperature of -56℃ and a vacuum degree of 10 Pa for 72 h, labeled as ZIF-8-DA / GA.
[0047] Example 2 Preparation of dopamine hybrid ligand ZIF-8 / gelatin composite aerogel.
[0048] S1. Preparation of dopamine hybrid ligand ZIF-8 (ZIF-8-DA):
[0049] Weigh 5.17 g Zn(NO3)2·6H2O and 0.532 g dopamine hydrochloride and dissolve them in 132 mL deionized water as solution A, dissolve 49.26 g 2-methylimidazole in 400 mL deionized water as solution B, then quickly pour solution A into solution B and stir for 10 min. After mixing, the molar ratio of Zn(NO3)2·6H2O, 2-methylimidazole and water is 1:30:2400, and the concentration of dopamine hydrochloride is 1 mg / mL. Then, the reaction was immersed at 40℃ for 3 h to cause coordination cross-linking reaction, and the obtained precipitate was washed with ethanol solution and centrifuged to remove impurities. Finally, dopamine hybrid ligand ZIF-8 was obtained by drying and grinding, marked as ZIF-8-DA.
[0050] S2. Preparation of dopamine hybrid ligand ZIF-8 / gelatin composite aerogel ZIF-8-DA / GA:
[0051] 1wt% ZIF-8-DA was homogenously dispersed in 50 mL of deionized water at 6000 rpm, and then 1 g of gelatin was added and stirred at 300 rpm at 40℃ until completely dissolved. 0.5wt% of the crosslinker 3-glycidyloxypropyltriethoxysilane was dropped into the obtained slurry and stirred for 4 h at 50℃ to promote chemical crosslinking. Subsequently, 0.2wt% glutaraldehyde solution was added to further enhance the gelation process. The obtained hybrid hydrogel was placed in a PE mold for freeze-thaw treatment, frozen at -30℃ for 3 h, and then thawed at 4℃ for 12 h. The sample was then placed on a copper plate with liquid nitrogen at the bottom and oriented pre-frozen. Finally, the composite aerogel was prepared by vacuum freeze drying at a cold trap temperature of -56℃ and a vacuum degree of 10 Pa for 72 h, labeled as ZIF-8-DA / GA.
[0052] Example 3 Preparation of dopamine hybrid ligand ZIF-8 / gelatin composite aerogel.
[0053] S1. Preparation of dopamine hybrid ligand ZIF-8 (ZIF-8-DA):
[0054] 5.17 g Zn(NO3)2·6H2O and 1.62 g dopamine hydrochloride were weighed and dissolved in 140 mL deionized water as solution A, and 49.27 g 2-methylimidazole was dissolved in 400 mL deionized water as solution B. Then solution A was quickly poured into solution B and stirred for 60 min. After mixing, the molar ratio of Zn(NO3)2·6H2O, 2-methylimidazole and water was 1:60:3000, and the concentration of dopamine hydrochloride was 3 mg / mL. Then, it was immersed at 50℃ for 6 h to undergo coordination crosslinking reaction, and the precipitate was washed with ethanol solution and centrifuged to remove impurities. Finally, dopamine hybrid ligand ZIF-8 was obtained after drying and grinding, which was marked as ZIF-8-DA.
[0055] S2. Preparation of dopamine hybrid ligand ZIF-8 / gelatin composite aerogel ZIF-8-DA / GA:
[0056] 3 wt% ZIF-8-DA was homogenously dispersed in 50 mL deionized water at 10000 rpm, and then 1 g gelatin was added and stirred at 40℃ and 300 rpm until completely dissolved. 0.5 wt% crosslinker 3-glycidyloxypropyltriethoxysilane was added to the obtained slurry and stirred for 5 h at 40℃ to promote chemical crosslinking. Subsequently, 0.3 wt% glutaraldehyde solution was added to further enhance the gelation process. The obtained hybrid hydrogel was placed in a PE mold for freeze-thaw treatment, frozen at -20℃ for 6 h, and then thawed at 4℃ for 10 h. The sample was then placed on a copper plate with liquid nitrogen at the bottom and oriented pre-frozen. Finally, the composite aerogel was obtained by vacuum freeze drying at a cold trap temperature of -56℃ and a vacuum degree of 10 Pa for 72 h, which was labeled as ZIF-8-DA / GA.
[0057] Example 4 Preparation of dopamine hybrid ligand ZIF-8 / gelatin composite aerogel.
[0058] S1. Preparation of dopamine hybrid ligand ZIF-8 (ZIF-8-DA):
[0059] Weigh 5.17 g Zn(NO3)2·6H2O and 1.872 g dopamine hydrochloride and dissolve them in 168 mL deionized water as solution A, and dissolve 57.48 g 2-methylimidazole in 300 mL deionized water as solution B. The total volume of water is then poured into solution A and stirred for 60 min. After mixing, the molar ratio of Zn(NO3)2·6H2O, 2-methylimidazole and water is 1:70:2600, and the concentration of dopamine hydrochloride is 3 mg / mL. Then, it is immersed at 60℃ for 1 h to undergo coordination and cross-linking reaction. The obtained precipitate is washed with ethanol solution and centrifuged to remove impurities. Finally, dopamine hybrid ligand ZIF-8 is obtained by drying and grinding, which is marked as ZIF-8-DA.
[0060] S2. Preparation of dopamine hybrid ligand ZIF-8 / gelatin composite aerogel ZIF-8-DA / GA:
[0061] 4wt% ZIF-8-DA was homogenously dispersed in 50 mL of deionized water at 8000 rpm, and then 1g of gelatin was added and stirred at 40℃ and 300 rpm until completely dissolved. 1wt% of the crosslinker 3-glycidyloxypropyltriethoxysilane was dropped into the obtained slurry and stirred for 3 h at 60℃ to promote chemical crosslinking. Subsequently, 0.5wt% glutaraldehyde solution was added to further enhance the gelation process. The obtained hybrid hydrogel was placed in a PE mold for freeze-thaw treatment, frozen at -20℃ for 6 h, and then thawed at 4℃ for 6 h. The sample was then placed on a copper plate with liquid nitrogen at the bottom and oriented pre-frozen. Finally, the composite aerogel was prepared by vacuum freeze drying at a cold trap temperature of -56℃ and a vacuum degree of 10 Pa for 72 h, labeled as ZIF-8-DA / GA.
[0062] Comparative Example 1 Preparation of ZIF-8 / gelatin composite aerogel.
[0063] The ZIF-8 was obtained without adding dopamine hydrochloride (DA) ligand in Example 1, and the remaining steps were the same as in Example 1 to prepare ZIF-8 / GA aerogel.
[0064] Comparative Example 2 Preparation of pure gelatin aerogel.
[0065] In Example 1, the ZIF-8-DA reinforcement phase was not added, and the remaining steps were the same as in Example 1 to prepare pure gelatin GA aerogel.
[0066] Experimental Example 1 The properties of the materials prepared in Example 1 and Comparative Example 1 were examined.
[0067] The scanning electron microscope images, X-ray diffraction images and infrared spectra of the dopamine hybrid ligand ZIF-8 prepared in Example 1 and the ZIF-8 prepared in Comparative Example 1 were analyzed.
[0068] Figure 1 The following are scanning electron microscope images of ZIF-8-DA and ZIF-8. The ZIF-8 particles are cubic in shape with an average particle size of 100 nm. In contrast, the ZIF-8-DA particles covalently bound to dopamine are rhombic dodecahedral in structure with an average diameter of 500 nm. This morphological change is mainly due to the addition of dopamine, which slows down the coordination between 2-methylimidazole and zinc ions, thereby reducing the nucleation rate of the particles and making the morphology of ZIF-8-DA more regular, which is conducive to uniform dispersion in the subsequent composite aerogel.
[0069] Figure 2 The X-ray diffraction patterns of ZIF-8-DA and ZIF-8, in which the main diffraction peaks of 2θ values are consistent, indicating that the addition of dopamine ligands does not change the basic crystal structure of ZIF-8, and it belongs to Zn-MOF material.
[0070] Figure 3 The infrared spectra of ZIF-8-DA and ZIF-8 are shown in Figure 1. ZIF-8-DA shows an infrared range of 3100-3600 cm -1 In addition, a typical broad absorption band at 1580 cm-1 was observed in ZIF-8-DA, which is mainly attributed to the stretching vibration of NH and OH bonds. -1 (C=N stretching vibration), 1142 and 998 cm -1 (CN stretch absorption) and the typical 421 cm -1 This indicates that the dopamine ligand is combined with ZIF-8 to form a Zn-containing 2+ -Dopamine and Zn 2+ -ZIF-8-DA hybrid crystals with dual coordination structure of dimethylimidazole. In addition, the introduction of dopamine ligands also introduced additional functional groups into ZIF-8, which not only improved the biocompatibility of MOF, but also provided abundant binding sites for the subsequent chemical cross-linking of composite aerogels.
[0071] Therefore, the ZIF-8-DA prepared in this scheme shows high dispersibility, stability and rich chemical functional group activity, which has a positive effect on the mechanical characteristics, structural stability and thermal insulation and flame retardant properties of the composite aerogel.
[0072] Experimental Example 2 The properties of the aerogels prepared in Example 1 and Comparative Examples 1-2 were examined.
[0073] The microscopic morphology characteristics of the ZIF-8-DA / GA composite aerogel of Example 1 and the aerogel of Comparative Examples 1-2 were investigated. Figure 4 , as shown in 5.
[0074] The ZIF-8-DA / GA composite aerogel exhibits a honeycomb porous structure with closely arranged pores and relatively uniform pore sizes, mainly between 50-100 μm. The ZIF-8-DA nanoparticles are evenly anchored on the interconnected gelatin porous network skeleton, enriching the pore structure of the aerogel, thereby significantly improving the overall mechanical properties and structural stability of the material. Figure 5 The protrusions on the skeleton surface of ZIF-8 / GA aerogel A are attributed to the uneven aggregation of ZIF-8 particles with poor dispersion. Figure 5 The gelatin GA aerogels of B have pore sizes of different sizes and smooth pore wall characteristics. Therefore, the ZIF-8-DA / GA composite aerogels synthesized by the novel multi-crosslinking strategy contain the porous pores of gelatin and the microporous pore characteristics of nano-MOF particles, presenting a unique three-dimensional porous microstructure.
[0075] Experimental Example 3 The mechanical characteristics of the ZIF-8-DA / GA composite aerogels of Examples 1-4 and the aerogels of Comparative Examples 1-2 were investigated.
[0076] Figure 6 is the stress-strain curve of the aerogel. Table 1 shows the compression modulus and maximum compression strength of the corresponding samples. The results show that these aerogels have typical compression characteristics of porous materials, undergoing an elastic deformation stage under low stress, followed by a plastic yield stage, and finally a densification stage. Compared with GA and ZIF-8 / GA aerogels, the stress of ZIF-8-DA / GA composite aerogels under 0-10% compression increases faster, and its compression modulus and maximum compression strength are 1.24-2.90 MPa and 0.66-1.65 MPa, respectively, which are twice and five times the maximum of GA aerogels. This shows that ZIF-8-DA, as a nano-reinforcement phase, significantly improves the mechanical properties of ZIF-8-DA / GA composite aerogels.
[0077]
[0078] Experimental Example 4 The chemical interaction between the ZIF-8-DA / GA composite aerogel of Example 2 and the ZIF-8 / GA aerogel of Comparative Example 1 was investigated.
[0079] Figure 7 A shows the C1s high-resolution spectra of gelatin-based aerogels and composite aerogels. In the composite aerogel, the C1s signal can be decomposed into three independent peaks located at 284.57 eV, 285.62 eV, and 287.42 eV, corresponding to the presence of C=C / CC, CN, and C=O / CO bonds. Compared with GA aerogels, the peak of C=O / CO bonds in ZIF-8-DA / GA composite aerogels shifts slightly to the right, indicating that there is a significant interaction between gelatin and ZIF-8-DA, which may be achieved through coordination bonds or hydrogen bonds. Figure 7 The N1s spectrum in B further reveals the chemical environment of nitrogen in the composite aerogel, showing two main peaks: 399.3 eV and 400.6 eV, corresponding to pyridinic nitrogen and pyrrolic nitrogen, respectively. This is the component that constitutes the structural unit of ZIF-8-DA, and its imidazole group and nitrogen atoms in dopamine are closely related to Zn 2+ The ions formed coordination bonds and constructed the skeleton structure of ZIF-8-DA. The increase in the N peak area in the composite aerogel was mainly due to the further enhancement of ZIF-8-DA and chemically cross-linked amide bonds (-NHCO-) in the composite aerogel.
[0080] Experimental Example 5 The thermal insulation and flame retardant physical parameters of the aerogels of Examples 1-4 and Comparative Examples 1-2 were examined.
[0081] Table 2 shows the physical parameters of the aerogels prepared in Examples 1-4 and Comparative Examples 1-2. The density of the ZIF-8-DA / GA composite aerogel is relatively low, ranging from 0.04 to 0.06 g / cm 3 , which is related to the amount of MOF particles added. Compared with the volume shrinkage of pure gelatin (13.7%), the minimum volume shrinkage of the composite aerogel is only 4.9%, which is attributed to the synergistic enhancement effect of ZIF-8-DA, which effectively reduces the collapse tendency of the internal pores, thereby reducing the volume shrinkage. In addition, the ZIF-8-DA / GA composite aerogel has a large specific surface area, which is 154.58-433.71 m 2 / g, while gelatin aerogel has no nanostructure and the specific surface area cannot be detected. The thermal conductivity of gelatin aerogel is 38.19 mW / m·K. In comparison, the thermal conductivity of ZIF-8-DA / GA composite aerogel is lower. The optimal value is 32.98 mW / m·K. The results show that ZIF-8-DA / GA nanoparticles and three-dimensional pore structure affect the thermal insulation properties of composite aerogels. On the one hand, the nano-MOF attached to the surface of the gelatin skeleton has a high specific surface area, which can significantly inhibit gas-phase thermal conductivity. At the same time, the lightweight density and porous structure will also reduce solid-phase thermal conductivity, thereby showing a lower overall thermal conductivity.
[0082]
[0083] Observe the infrared thermal imaging of ZIF-8-DA / GA composite aerogel. Heat the pure gelatin aerogel and the composite aerogel on a heat source of 100 degrees Celsius for 1 hour, and use an infrared thermal imager to record the cold surface temperature of the aerogel at steady state. The results are as follows: Figure 8 As shown in the figure, the cold surface temperature of pure gelatin aerogel is about 56°C, and the cold surface temperature of composite aerogel is about 49.8°C. It can be seen that ZIF-8-DA / GA composite aerogel can effectively inhibit the heat transfer between the internal structures of aerogel and greatly reduce the temperature rise change in the axial direction.
[0084] Experimental Example 6 The thermal stability of the ZIF-8-DA / GA composite aerogel of Example 2 and the aerogel of Comparative Examples 1-2 was investigated.
[0085] Fig. 9 The results show that the weight loss of GA aerogels is mainly due to the loss of surface water at lower temperatures (about 100°C) and the significant degradation of the main and side chains of the polymers in the medium and high temperature stages (400-600°C), with a mass loss of nearly 93% at 800°C. For ZIF-8-DA / GA and ZIF-8 / GA composite aerogels, all thermogravimetric analyses involve three stages. The first stage occurs in the temperature range of 30 to 200°C, with a weight loss of about 12%. The weight loss in this stage is related to the evaporation of water adsorbed on the sample surface and the thermal decomposition of MOF organic ligands. The second stage of thermogravimetric analysis occurs in the temperature range of 250 to 450°C, which is mainly due to the decomposition and oxidation of ZnO formed by ZIF-8-DA embedded in the gelatin skeleton surface, and the rapid charring mass loss of the organic polymer covered on the surface. Since ZIF-8-DA has a more stable hybrid ligand crystal structure than ZIF-8, the thermal decomposition rate of ZIF-8-DA / GA is lower than that of ZIF-8 / GA composite aerogels. The high temperature of 500-600°C in the third stage causes the organic skeleton structure to degrade rapidly. The addition of Zn-MOF-DA slows down the pyrolysis of the organic matrix by forming a protective layer, while the ZnO produced by its decomposition covers the polymer surface at high temperatures, enhancing the carbonization stability of the organic skeleton, thereby reducing mass loss and improving the heat resistance of the overall structure.
[0086] Experimental Example 7 investigates the actual flame retardant properties of the ZIF-8-DA / GA composite aerogel of Example 2 and the aerogels of Comparative Examples 1-2.
[0087] The results are as follows Fig.10 As shown in the figure, GA aerogel has an open flame after being exposed to the flame for 5 seconds, and its block shrinks violently, and a large amount of smoke is generated during the combustion process. No surface open flames were seen in ZIF-8 / GA and ZIF-8-DA / GA composite aerogels during the combustion process, but ZIF-8-DA / GA has the smallest volume shrinkage and the smallest smoke production compared with GA and ZIF-8 / GA aerogels. It can be seen that the composite of ZIF-8-DA enhances the fire resistance of gelatin aerogel, and the ZnO metal oxides and non-combustible substances produced during the combustion process reduce the oxygen concentration of the internal structure, aggravate the carbonization of the aerogel surface, and the microstructure of the nanomaterial itself inhibits heat and material transfer, thereby reducing the flammability of the material.
[0088] The above is only a preferred embodiment of the present invention, and the protection scope of the present invention is not limited to the above embodiments. For those skilled in the art, improvements and changes obtained without departing from the technical concept of the present invention should also be regarded as the protection scope of the present invention.
Claims
1. A method for preparing a dopamine hybrid ligand ZIF-8 / gelatin composite aerogel, characterized in that: The following steps are involved: S1. Preparation of dopamine hybrid ligand ZIF-8: zinc salt and dopamine hydrochloride are dissolved in deionized water as solution A, 2-methylimidazole is dissolved in deionized water as solution B, then solution A is poured into solution B and stirred rapidly to cause coordination cross-linking reaction, the obtained precipitate is washed with ethanol solution, centrifuged to remove impurities, and dried and ground to obtain dopamine hybrid ligand ZIF-8, which is marked as ZIF-8-DA; S2. Preparation of dopamine hybrid ligand ZIF-8 / gelatin composite aerogel: the dopamine hybrid ligand ZIF-8 prepared in step S1 is homogenized at high speed in a deionized water solution, gelatin is added and stirred until completely dissolved, a cross-linking agent is dripped into the obtained slurry and continuously stirred for chemical cross-linking reaction, a glutaraldehyde solution is added and stirred, the obtained mixed hydrogel is placed in a PE mold for freeze-thaw treatment, and then thawed, and then the sample is placed on a copper plate with liquid nitrogen at the bottom and directional pre-frozen, and finally, a dopamine hybrid ligand ZIF-8 / gelatin composite aerogel ZIF-8-DA / GA is prepared by vacuum freeze-drying; In step S2, the crosslinking agent is 3-glycidyloxypropyltriethoxysilane, the addition amount is 0.1-1wt%, the temperature of the chemical crosslinking reaction is 40-60°C, the continuous stirring time is 3-6 h, the concentration of the glutaraldehyde solution is 0.1-0.5 wt%, and the stirring time of adding the glutaraldehyde solution is 5 min.
2. The preparation method according to claim 1, characterized in that: The zinc salt in step S1 is Zn(NO3)2·6H2O, the molar ratio of the zinc salt to 2-methylimidazole and deionized water is 1:30-70:2000-3000, and the concentration of dopamine hydrochloride is 1-4 mg / mL.
3. The preparation method according to claim 1, characterized in that: The rapid stirring time in step S1 is 5-60 minutes, and the coordination cross-linking reaction temperature is 30-60° C. and the time is 1-20 hours.
4. The preparation method according to claim 1, characterized in that: The dopamine hybrid ligand ZIF-8 prepared in step S1 is a rhombic dodecahedron structure with an average diameter of 500 nm.
5. The preparation method according to claim 1, characterized in that: In the step S2, the addition amount of the dopamine hybrid ligand ZIF-8 is 1-4 wt %, the homogenization speed is 4000-10000 rpm, the concentration of gelatin is 2 wt %, the dissolution temperature is 40° C., and the stirring speed is 300-600 rpm.
6. The preparation method according to claim 1, characterized in that: The temperature of the freeze-thaw treatment in step S2 is -40°C to -20°C, the time is 2-6 h, the thawing temperature is 4°C, the time is 12-24 h; the cold trap temperature of the vacuum freeze-drying is -56°C, the vacuum degree is below 10 Pa, and the time is 72 h.
7. A dopamine hybrid ligand ZIF-8 / gelatin composite aerogel prepared by the preparation method according to any one of claims 1 to 6.
8. Use of the dopamine hybrid ligand ZIF-8 / gelatin composite aerogel prepared by the preparation method according to any one of claims 1 to 6 in the preparation of thermal insulation and flame retardant materials.
Citation Information
Patent Citations
A kind of MOF-loaded aramid nanofiber aerogel and its preparation method and application
CN116446183B
Biomass aerogel-based heat-insulation flame-retardant material and preparation method thereof
CN117247682A
Dopamine-based surface modification method of polymeric membrane
CN111420559A
Gel-Ale-Mg-coated PDA gel scaffold material as well as preparation method and application thereof
CN115970053A